The halloween tree ebook - Bradbury, Ray (2015)
Make storytime a little spookier with fantasy master Ray Bradbury as he takes readers on a riveting trip though space and time to discover the true origins of Halloween. Join the shadowy Carapace Clavicle Moundshroud as he takes eight trick-or-treaters on an unforgettable journey to find their missing friend, Pip. Travel through space and time, from the tombs of ancient Egypt to the gargoyles of Notre-Dame Cathedral, all the way to the cemeteries of Mexico on el Día de Los Muertos, the Day of the Dead. Is Pip still alive? And if so, can his friends save him from a ghastly fate before it’s too late? "If you want to know what Halloween is, or if you simply want an eerie adventure, take this mystery history trip. You couldn't ask for better than master fantasizer Ray Bradbury." — The Boston Globe